Restoration of liver insulin signaling in Insr knockout mice fails to normalize hepatic insulin action - Okamoto, Haruka (American Society for Clinical Investigation, 2005)
Partial restoration of insulin receptor Insr expression in brain, liver, and pancreatic β cells is sufficient for rescuing Insr knockout mice from neonatal death, preventing diabetes ketoacidosis, and normalizing life span and reproductive function. However, the transgenically rescued mice (referred to as L1) have marked hyperinsulinemia, and approximately 30% develop late-onset type 2 diabetes. Analyses of protein expression indicated that L1 mice had modestly reduced Insr content but normal insulin-stimulated Akt phosphorylation in the liver. Conversely, L1 mice had a near complete ablation of Insr protein product in the arcuate and paraventricular nuclei of the hypothalamus, which was associated with a failure to undergo insulin-dependent Akt phosphorylation in the hypothalamus. To test whether reconstitution of insulin signaling in the liver is sufficient for restoring in vivo hepatic insulin action, we performed euglycemic hyperinsulinemic clamp studies in conscious L1 and WT mice. During the clamp, L1 mice required an approximately 50% lower rate of glucose infusion than did WT controls, while the rate of glucose disappearance was not significantly altered. Conversely, the rate of glucose production was increased approximately 2-fold in L1 mice. Thus, restoration of hepatic insulin signaling in Insr knockout mice fails to normalize the in vivo response to insulin.